PEMANFAATAN BUAH PISANG MASAK SEHARI DAN KELOPAK BUNGA ROSELLA DALAM PEMBUATAN SELAI - Putra Mayzent Manik; Vonny Setiaries Johan; Rahmayuni Rahmayuni (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2017)
The purpose of this study wasto obtain the best jam formulation from masak sehari banana cultivar and rosella petals and preferred by the panelists. This research wascarriedexperimentallyusingcompletely randomizeddesign(CRD) withfive treatments and threereplications. The treatments in this study werePR1(80%banana fruit and  rosella petals), PR2(65% banana fruitand35%  rosella petals ), PR3(50%  banana fruitand50%rosellapetals), PR4(35%  banana fruitand65% petals rosela)andPR5(20%  banana fruit and 80% rosella petals). Data obtained were treated by ANOVA followed by Duncan New Multiple Range Test (DNMRT) the level of 5%. The results showed that the ratio of banana and rosella petals significantly effect on the water content, acidity, total dissolved solids, fiber contents, sucrose content, pectin content and sensory test. The best jam of this study was PR3 (50% banana fruit and 50% rosella petals). This jam contained water content 31.33%; pH 3.86; total dissolved solids 65.56%; fiber content 2.91%; sucrose content 52.19% and pectin content 1.05%. The jam had red colour, rather taste of banana and rather taste of rosella petals, rather flavor of banana and rather flavor of rosella petals and rather soft texture.Keywords: Jam, Masak sehari banana cultivar, rosella petals.